Price formation and liquidity provision in short-term fixed income markets - Chris D'Souza; Ingrid Lo; Stephen Sapp (Bank of Canada, 2007)
Differences in market structures may affect the manner in which fundamental information is incorporated into prices. High levels of quote and trade transparency plus substantial quoting obligations in European government securities markets ensure that prices are informationally efficient. The relationship between price changes, order flow, relative depth and spreads across European and Canadian short-term government bond markets is examined via a reduced-form vector autoregression model. In European markets, dealers are able to quickly absorb private information elsewhere in the market. Consequently, spreads and the relative depth on the bid and offer sides of the market are found to be only slightly informative. Similarly, order flow, which reflects inventory management practices in addition to private information, explains a smaller proportion of the variation in asset returns in European markets than in Canadian interdealer brokered markets where no quoting obligations exist.
Keywords: G12; G14; G15; 330; Market structure and pricing; Financial markets; Interest rates; Finanzmarkt; Marktstruktur; Öffentliche Anleihe; Zins; VAR-Modell; EU-Staaten; Kanada